Nanocrystalline blue ceramic corundum abrasive and method for producing same
Patent Information
- Application Number
- CN202611221521.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]上述方法虽然能够获得蓝色陶瓷刚玉,但仍存在以下问题:可溶性钴盐直接混入含大量水分的氧化铝溶胶时,在干燥过程中容易随水分迁移并向颗粒表层或干燥裂纹周围富集
[0052]与现有技术相比,本发明提供了一种纳米晶蓝色陶瓷刚玉磨料及其制备方法,具备以下有益效果:通过Co-Al层状双氢氧化物在α-Al2O3晶种核表面原位生长,使钴显色前驱体受到固体界面限域,降低钴组分在凝胶干燥过程中的迁移和局部富集,提高不同磨粒之间的颜色一致性。
Smart Images

Figure CN122977819A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic materials technology, specifically to a nanocrystalline blue ceramic corundum abrasive and its preparation method. Background Technology
[0002] Ceramic corundum abrasives are typically prepared using boehmite as an alumina precursor through steps such as sol-gel, gelation, drying, crushing, calcination, and sintering. Compared to fused alumina, sol-gel ceramic corundum can form submicron or nanoscale α-Al₂O₃ grains within its interior. Under grinding loads, it can undergo micro-fracture and continuously form new cutting edges, thus possessing both high toughness and self-sharpening properties.
[0003] Introducing cobalt into ceramic corundum can produce a blue appearance by forming cobalt aluminum spinel. Blue can not only serve as an identification feature for ceramic corundum products, but also be used to observe the distribution of abrasive grains in grinding wheels, coated abrasives, or grinding debris.
[0004] Existing blue ceramic corundum typically introduces coloring components using the following methods: First, cobalt nitrate, cobalt acetate, or cobalt oxide are directly added to a pseudoboehmite sol or gel, allowing the cobalt component to react with alumina during subsequent sintering; second, ceramic corundum particles are prepared first, and then cobalt salts or cobalt-aluminum pigments are coated on the surface of the abrasive particles and subjected to secondary heat treatment; third, cobalt salts, seed crystals, and sintering control components such as magnesium and yttrium are added to alumina sol separately and mixed by mechanical stirring or ball milling.
[0005] While the above method can produce blue ceramic corundum, it still has the following problems: When soluble cobalt salts are directly mixed into alumina sol containing a large amount of water, they tend to migrate with the moisture during the drying process and accumulate on the particle surface or around drying cracks. Local differences in cobalt ion concentration can cause uneven size and distribution of the colored hue, resulting in significant color differences between different batches of abrasives and between different areas of the same abrasive grain. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention provides a nanocrystalline blue ceramic corundum abrasive and its preparation method. By growing Co-Al layered double hydroxides in situ on the surface of α-Al2O3 seed nuclei, the cobalt color precursor is confined by the solid interface, reducing the migration and local enrichment of cobalt components during the gel drying process, and improving the color consistency among different abrasive grains.
[0007] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing nanocrystalline blue ceramic corundum abrasive, comprising the following steps:
[0008] Step S1: Using α-Al2O3 particles with an average particle size of 20-80 nm as seed nuclei, a discontinuous Co-Al layered double hydroxide inner layer is grown in situ on the surface of the seed nuclei; then, an outer layer of Mg-Y-Al citric acid polymer complex is formed on the outside of the Co-Al layered double hydroxide inner layer to obtain a surface-confined composite seed.
[0009] Based on the mass of Al2O3 in the final abrasive, the amount of α-Al2O3 seed nuclei added is 0.15-0.60 wt%, the cobalt content in the inner layer of Co-Al layered double hydroxide is 0.04-0.20 wt% (calculated as CoO), the magnesium content in the outer layer of Mg-Y-Al citric acid polymer complex is 0.05-0.25 wt% (calculated as MgO), and the yttrium content is 0.02-0.12 wt% (calculated as Y2O3).
[0010] The "discontinuous inner layer" refers to the Co-Al layered double hydroxides distributed on the surface of the α-Al2O3 seed nucleus in the form of nanosheets, nanoislands, or nanoclusters that are separated or partially connected, rather than forming a completely continuous and dense coating film.
[0011] The "discontinuous outer layer" refers to the Mg-Y-Al citric acid polymer complex being distributed on the outer side of the Co-Al layered double hydroxide inner layer in the form of local coating, bridging, or island deposition, so that the surface of the composite seed crystal still retains an area that can contact the pseudoboehmite sol.
[0012] Step S2: Mix boehmite, water and nitric acid to prepare a boehmite sol with a solid content of 18-30 wt% and a pH of 2.8-4.2.
[0013] The surface-confined composite seed crystals obtained in step S1 are dispersed in a pseudo-boehmite sol, and after shear dispersion, vacuum degassing and heating aging, alumina wet gel containing composite seed crystals is obtained.
[0014] Step S3: Extrude the alumina wet gel containing composite seed crystals into shape, perform the first stage of drying at a lower temperature and controlled relative humidity, and then perform the second stage of drying at a higher temperature and reduced pressure.
[0015] The dried gel was crushed and sieved to obtain ceramic corundum precursor particles.
[0016] Step S4: Place the ceramic corundum precursor particles in an oxygen-containing atmosphere for organic matter removal and pre-reaction calcination.
[0017] During the pre-reaction process, the Co-Al layered double hydroxide is first converted into a cobalt-aluminum mixed oxide, and then further reacts with the adjacent α-Al2O3 seed nucleus and the alumina formed by gel conversion to form a cobalt-aluminum spinel nanocrystal domain containing CoAl2O4; the Mg-Y-Al citric acid polymer complex is converted into a grain boundary regulating phase precursor containing magnesium, yttrium and aluminum.
[0018] The particles were then rapidly heated to 1250–1340°C for short-term densification sintering, and then cooled to 1080–1160°C for grain boundary stabilization treatment. After cooling, sieving, and classification, nanocrystalline blue ceramic corundum abrasive was obtained.
[0019] Furthermore, the α-Al₂O₃ seed nuclei were prepared according to the following method:
[0020] α-Al2O3 powder with a purity of not less than 99.9 wt% and a median particle size of 0.2–1.0 μm was added to a nitric acid aqueous solution to prepare a slurry with a solid content of 5–15 wt% and a pH value of 3.0–4.2. Yttrium-stabilized zirconia grinding balls with a particle size of 0.05–0.15 mm were added for wet grinding until the median particle size of the α-Al2O3 particles was 20–80 nm.
[0021] Add 0.20–0.80 wt% polyaspartic acid relative to the mass of α-Al2O3 to the ground slurry, and stir at 30–50 °C for 20–90 min to allow the polyaspartic acid to adsorb onto the surface of the α-Al2O3 particles, thus obtaining a surface-carboxylated α-Al2O3 seed nucleus dispersion.
[0022] Furthermore, the Co-Al layered double hydroxide inner layer is prepared according to the following method:
[0023] Soluble cobalt salt, soluble aluminum salt, and urea were added to the α-Al2O3 seed nucleus dispersion. The molar ratio of cobalt ions to aluminum ions was 2.0:1 to 3.2:1, the total concentration of cobalt ions and aluminum ions was 0.01 to 0.06 mol / L, and the molar ratio of urea to the total amount of cobalt ions and aluminum ions was 6:1 to 15:1.
[0024] The resulting mixture was reacted at 85–98 °C for 4–10 h to gradually increase the pH value of the system to 7.5–9.0, and to allow the Co-Al layered double hydroxide to preferentially nucleate on the surface of the α-Al2O3 seed nucleus, forming a discontinuous nanosheet inner layer with a local thickness of 2–10 nm.
[0025] The soluble cobalt salt is at least one of cobalt nitrate and cobalt acetate; the soluble aluminum salt is at least one of aluminum nitrate and aluminum acetate.
[0026] Furthermore, the outer layer of the Mg-Y-Al citric acid polymer complex was prepared according to the following method:
[0027] Magnesium nitrate, yttrium nitrate, and aluminum nitrate were dissolved in a mixed solvent of water and ethanol, and then citric acid and ethylene glycol were added to obtain a Mg-Y-Al complex solution.
[0028] The molar ratio of magnesium, yttrium and aluminum is 3-8:1:4-12, the molar ratio of citric acid to the total amount of magnesium, yttrium and aluminum is 1.2-2.0:1, and the molar ratio of ethylene glycol to citric acid is 0.5-1.5:1.
[0029] The pH of the Mg-Y-Al complex solution was adjusted to 5.5–6.5, and α-Al2O3 seed nuclei with an inner layer of Co-Al layered double hydroxides on the surface were added. The solution was stirred and concentrated at 70–85 °C under reduced pressure to allow citric acid and ethylene glycol to undergo condensation polymerization, and the Mg-Y-Al polymer complex was adsorbed onto the outer side of the inner layer of Co-Al layered double hydroxides, forming a discontinuous outer layer with a local thickness of 1–8 nm.
[0030] Further, the material after the outer layer is formed is vacuum dried at 60-85℃ to obtain composite seed powder; the composite seed powder is added to deionized water with a pH of 4.5-5.8, and ultrasonically dispersed and wet-milled in the presence of polyethylene glycol at 0.05-0.20 wt% relative to the mass of the composite seed powder to obtain a composite seed dispersion with a solid content of 5-15 wt%.
[0031] The median particle size D50 of the composite seed in the composite seed dispersion is 35–120 nm, and the D90 is no greater than 200 nm.
[0032] Furthermore, the purity of boehmite is not less than 99.5 wt%, the specific surface area is 180–320 m² / g, and the Na₂O content is not higher than 0.05 wt%.
[0033] The molar ratio of nitric acid to AlOOH in pseudoboehmite is 0.03 to 0.08:1.
[0034] First, add boehmite to an aqueous nitric acid solution and shear disperse it at 1500–3000 r / min for 20–60 min; then add a composite seed crystal dispersion and continue shear dispersion for 15–45 min; degas it under a vacuum of -0.080–-0.095 MPa for 10–30 min, and then age it at 45–65 °C for 1–4 h.
[0035] Furthermore, the alumina wet gel is extruded through a mold with a pore size of 0.3–1.2 mm, and then dried in the first stage for 2–6 hours at 45–60°C and 60–80% relative humidity, followed by a second stage of drying for 2–8 hours at 80–110°C and a vacuum degree of -0.070 to -0.095 MPa.
[0036] The dried gel was crushed and sieved to obtain ceramic corundum precursor particles with a particle size of 0.15–2.0 mm.
[0037] Furthermore, the pre-reaction calcination includes:
[0038] The temperature is increased to 350–450°C at a rate of 2–5°C / min and held for 0.5–1.5 h to remove the organic components from the polymer complex.
[0039] The temperature is then increased to 930–1050℃ at a heating rate of 5–10℃ / min and held for 0.5–1.5 h to allow the cobalt-aluminum mixed oxide to react with the adjacent alumina at the interface, forming primary cobalt-aluminum spinel crystal domains with an average size of 5–40 nm containing CoAl2O4.
[0040] Furthermore, the short-time densification sintering and grain boundary stabilization treatment includes:
[0041] The pre-reacted precursor particles were heated to 1270–1335°C at a heating rate of 15–40°C / min and held for 5–20 min.
[0042] Then, the temperature is lowered to 1100–1160°C at a rate of 20–60°C / min, held for 30–120 min, and then cooled to below 800°C at a rate of no more than 10°C / min, and then allowed to cool naturally to room temperature.
[0043] Furthermore, in the obtained nanocrystalline blue ceramic corundum abrasive, α-Al2O3 constitutes a continuous matrix phase, and the average size of α-Al2O3 grains is 80–250 nm; the average size of the CoAl2O4-containing cobalt aluminum spinel nanocrystal domains is 10–60 nm.
[0044] Based on the total mass of the final abrasive, the calculated content of CoO is 0.04–0.20 wt%, the content of MgO is 0.05–0.25 wt%, the content of Y2O3 is 0.02–0.12 wt%, and the balance is Al2O3 and unavoidable impurities.
[0045] This invention does not simply mix seed crystals, cobalt salts, and sintering aids, but rather pre-organizes the three types of functional components onto the same composite seed crystal.
[0046] α-Al2O3 seed nuclei provide heterogeneous nucleation sites for the transformation of boehmite to α-Al2O3, enabling the phase transformation to occur simultaneously at more sites and reducing the coarse grains caused by the preferential growth of a small number of nuclei.
[0047] After polyaspartic acid is adsorbed onto the surface of α-Al2O3 seed nuclei, it improves the dispersion stability of the seed nuclei in the aqueous phase. On the other hand, it utilizes the adsorption effect of carboxyl groups on cobalt and aluminum ions to allow Co-Al layered double hydroxides to preferentially grow on the surface of the seed nuclei, reducing free precipitation.
[0048] After pre-reaction, the Co-Al layered double hydroxide forms a cobalt-aluminum mixed oxide, and further forms CoAl2O4 cobalt-aluminum spinel nanocrystal domains near the interface between the α-Al2O3 seed nucleus and the alumina matrix. This establishes a spatial correlation between the location of the colored phase formation and the nucleation location of the α-Al2O3 phase transformation, reducing the macroscopic migration of the cobalt component during gel drying.
[0049] After heat treatment, the outer layer of the Mg-Y-Al citric acid polymer complex forms a highly dispersed precursor of magnesium, yttrium, and aluminum oxides or aluminates. As the grains grow, these components preferentially distribute near the grain boundaries, inhibiting abnormal grain growth through grain boundary segregation, second-phase pinning, and reduced grain boundary migration rates.
[0050] The pre-reaction step allows the removal of organic matter, the formation of primary cobalt-aluminum spinel crystal domains, and partial alumina phase transformation to occur before entering the high-temperature rapid densification stage, reducing the competition between the color development reaction and rapid grain growth at the same high temperature stage.
[0051] The short-term high-temperature stage mainly completes the particle densification, and then the temperature is lowered to the grain boundary stabilization temperature for holding, so that the grain boundary control components are further evenly distributed, while avoiding prolonged stay at the highest sintering temperature to prevent grain coarsening.
[0052] Compared with the prior art, the present invention provides a nanocrystalline blue ceramic corundum abrasive and its preparation method, which has the following beneficial effects: by growing Co-Al layered double hydroxides in situ on the surface of α-Al2O3 seed nuclei, the cobalt color precursor is confined by the solid interface, reducing the migration and local enrichment of cobalt components during the gel drying process, and improving the color consistency between different abrasive grains.
[0053] This invention enables the formation of CoAl2O4-containing cobalt aluminum spinel nanocrystalline domains primarily near the α-Al2O3 grain boundaries. Compared to free, large-sized cobalt aluminum spinel aggregates, the nanocrystalline domains near the grain boundaries provide blue coloration and are less prone to forming coarse, brittle inclusions that penetrate abrasive grains.
[0054] The outer layer of the Mg-Y-Al citric acid polymer complex allows the Mg and Y components to be pre-distributed around the composite seed crystals, making it easier for them to enter the grain boundary region during the growth of alumina grains. This reduces the proportion of abnormal grains and enables the abrasive grains to disperse and undergo controllable micro-fracture when subjected to stress.
[0055] Pre-reaction, short-time densification, and grain boundary stabilization treatments divide the formation of colored phases, particle densification, and grain boundary regulation into interconnected stages, which can shorten the holding time at the highest temperature and suppress excessive growth of α-Al2O3 grains while maintaining particle density.
[0056] This invention does not rely solely on increasing the cobalt content to obtain a deep blue color, but rather achieves stable color development by improving the space utilization efficiency of cobalt. Therefore, good blue hue and batch uniformity can be obtained even at lower cobalt contents. The resulting ceramic corundum exhibits high ball milling toughness and fracture resistance while maintaining a nano- or submicron grain structure, making it suitable for bonded abrasives and coated abrasives. Attached Figure Description
[0057] Figure 1 This is a transmission electron microscope image of the surface-confined composite seed crystals in Example 2;
[0058] Figure 2 The HAADF-STEM-EDS elemental distribution diagram of the surface-confined composite seed crystal in Example 2 is shown. Detailed Implementation
[0059] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0060] Please see Figure 1 and Figure 2 This invention provides a technical solution for nanocrystalline blue ceramic corundum abrasive and its preparation method:
[0061] Figure 1 The markings are as follows: Region A represents the α-Al2O3 seed nucleus; Region B represents the discontinuous sheet-like or island-like coating area on the surface of the α-Al2O3 seed nucleus, corresponding to the area where the inner layer of Co-Al layered double hydroxide is located on the surface of the composite seed; Region C represents the lighter gray edge area outside Region B, corresponding to the area where the outer layer of the Mg-Y-Al citric acid polymer complex is located.
[0062] Figure 2The meanings of each element are as follows: The Al element diagram is used to characterize the aluminum-containing components in the α-Al₂O₃ seed nucleus and the inner Co-Al and outer Mg-Y-Al layers. The Co element diagram is used to characterize the cobalt-containing regions in the inner layer of the Co-Al layered double hydroxide. The Mg element diagram is used to characterize the magnesium-containing regions in the outer layer of the Mg-Y-Al citric acid polymer complex. The Y element diagram is used to characterize the yttrium-containing regions in the outer layer of the Mg-Y-Al citric acid polymer complex. The O element diagram is used to help characterize the overall distribution of oxides, hydroxides, and polymer complexes. The overlay diagram is used to visually represent the spatial relationships between Al, Co, Mg, and Y elements.
[0063] Unless otherwise specified, all embodiments are based on a final abrasive material with an equivalent mass of 1000g of Al2O3. Cobalt nitrate is represented by Co(NO3)2·6H2O, aluminum nitrate by Al(NO3)3·9H2O, magnesium nitrate by Mg(NO3)2·6H2O, yttrium nitrate by Y(NO3)3·6H2O, and cobalt acetate by Co(CH3COO)2·4H2O.
[0064] The purity of the boehmite used in each embodiment is not less than 99.5 wt%, and the Na2O content is not higher than 0.05 wt%.
[0065] Example 1:
[0066] S1-1:
[0067] Weigh 1.50g of α-Al2O3 powder with a purity of 99.95wt% and a median particle size of 0.20μm, add it to nitric acid aqueous solution, and prepare a slurry with a solid content of 5wt% and a pH value of 3.0.
[0068] Add yttrium-stabilized zirconia grinding balls with a particle size of 0.05 mm and grind in a wet grinding equipment until the median particle size of α-Al2O3 particles is 20 nm.
[0069] Add 0.003g of polyaspartic acid, i.e., the amount of polyaspartic acid is 0.20wt% of the mass of α-Al2O3, and stir at 30℃ for 20min to obtain α-Al2O3 seed nucleus dispersion.
[0070] S1-2:
[0071] Add 1.554g of cobalt nitrate hexahydrate, 1.001g of aluminum nitrate nonahydrate and 2.885g of urea to the seed nucleus dispersion, and add deionized water to make the total concentration of cobalt ions and aluminum ions 0.01mol / L.
[0072] The molar ratio of cobalt ions to aluminum ions is 2.0:1, and the molar ratio of urea to the total amount of cobalt and aluminum ions is 6:1.
[0073] The reaction was carried out at 85℃ for 4 hours, and the pH of the system was 7.5 at the end of the reaction. The mixture was centrifuged and washed with deionized water to obtain seed nuclei with a Co-Al layered double hydroxide inner layer on the surface.
[0074] S1-3:
[0075] 3.181g magnesium nitrate hexahydrate, 0.678g yttrium nitrate hexahydrate and 2.658g aluminum nitrate nonahydrate were dissolved in a mixed solvent of water and ethanol in a volume ratio of 6:4, and 4.902g anhydrous citric acid and 0.792g ethylene glycol were added.
[0076] The molar ratio of magnesium, yttrium and aluminum is 7.0:1:4.0, the molar ratio of citric acid to the total amount of metal ions is 1.2:1, and the molar ratio of ethylene glycol to citric acid is 0.5:1.
[0077] The pH of the system was adjusted to 5.5, and the material obtained from S1-2 was added. The mixture was stirred and concentrated at 70°C and 40 kPa absolute pressure to form a discontinuous outer layer with a local average thickness of 1.1 nm.
[0078] The composite seed powder was obtained by vacuum drying at 60℃.
[0079] The composite seed crystal powder was added to deionized water with a pH of 4.5, and 0.05 wt% polyethylene glycol was added relative to the mass of the composite seed crystal powder. After ultrasonic dispersion and wet grinding, a composite seed crystal dispersion with a solid content of 5 wt% was obtained. Its D50 was 35 nm and D90 was 78 nm.
[0080] The amounts of cobalt, magnesium, and yttrium added to the composite seed crystals are calculated based on the final Al2O3 mass as 0.04wt%CoO, 0.05wt%MgO, and 0.02wt%Y2O3, respectively.
[0081] S2:
[0082] Weigh 1174.34g of boehmite, add 56.93g of 65% nitric acid to deionized water, then add boehmite, replenish deionized water and include the water in the composite seed dispersion, so that the solid content of boehmite in the system is 18wt%.
[0083] Shear dispersion was performed at 1500 r / min for 20 min, and the pH of the system was adjusted to 2.8. The composite seed dispersion was added, and shear dispersion was continued for 15 min.
[0084] The alumina wet gel was obtained by vacuum degassing at -0.080 MPa for 10 min and then aging at 45 °C for 1 h.
[0085] S3:
[0086] The wet gel is extruded through a mold with a pore size of 0.3 mm.
[0087] Dry at 45℃ and 60% relative humidity for 2 hours, then dry at 80℃ and -0.070MPa vacuum for 2 hours.
[0088] The dried gel was crushed and sieved to obtain ceramic corundum precursor particles with a particle size of 0.15–0.60 mm.
[0089] S4:
[0090] In an air atmosphere, the temperature is increased to 350℃ at a rate of 2℃ / min and held for 0.5h; then increased to 930℃ at a rate of 5℃ / min and held for 0.5h.
[0091] The temperature was then increased to 1270℃ at a rate of 15℃ / min and held for 5 minutes; then decreased to 1100℃ at a rate of 20℃ / min and held for 30 minutes; then decreased to 800℃ at a rate of 8℃ / min and allowed to cool naturally.
[0092] The sintered material is crushed, shaped, and sieved to obtain nanocrystalline blue ceramic corundum abrasive with an F46 particle size.
[0093] Example 2:
[0094] S1-1:
[0095] Weigh 3.50g of α-Al2O3 powder with a purity of 99.95wt% and a median particle size of 0.60μm, and prepare a slurry with a solid content of 10wt% and a pH value of 3.6.
[0096] Yttrium-stabilized zirconia grinding balls with a particle size of 0.10 mm were added, and the mixture was wet-milled until the median particle size of α-Al2O3 particles was 50 nm.
[0097] Add 0.0175g of polyaspartic acid, which is 0.50wt% of the mass of α-Al2O3, and stir at 40℃ for 55min.
[0098] S1-2:
[0099] Add 4.661g of cobalt nitrate hexahydrate, 2.311g of aluminum nitrate nonahydrate and 13.983g of urea, and add water to make the total concentration of cobalt and aluminum ions 0.035mol / L.
[0100] The molar ratio of cobalt to aluminum is 2.6:1, and the molar ratio of urea to the total amount of metal ions is 10.5:1.
[0101] The reaction was carried out at 91.5℃ for 7 hours, and the pH value at the end of the reaction was 8.25. The local average thickness of the inner layer of the resulting Co-Al layered double hydroxide was 5.8 nm.
[0102] S1-3:
[0103] Dissolve 9.543g magnesium nitrate hexahydrate, 2.375g yttrium nitrate hexahydrate and 18.606g aluminum nitrate nonahydrate in a mixed solvent of water and ethanol, and add 28.593g anhydrous citric acid and 9.237g ethylene glycol.
[0104] The molar ratio of magnesium, yttrium, and aluminum is 6.0:1:8.0, the molar ratio of citric acid to the total amount of metal ions is 1.6:1, and the molar ratio of ethylene glycol to citric acid is 1.0:1.
[0105] The pH of the system was adjusted to 6.0, and the system was concentrated at 77.5℃ and 32kPa absolute pressure to form a discontinuous outer layer with a local average thickness of 4.6nm.
[0106] The resulting composite seed crystals were vacuum dried at 72.5℃, then added to water with a pH of 5.15, along with 0.125 wt% polyethylene glycol. The mixture was then ultrasonically and wet-milled to obtain a composite seed crystal dispersion with a solid content of 10 wt%. Its D50 was 75 nm, and its D90 was 142 nm.
[0107] The amount of composite seed crystals added is 0.35 wt% based on the final Al2O3 mass; the amounts of cobalt, magnesium, and yttrium added are converted to 0.12 wt% CoO, 0.15 wt% MgO, and 0.07 wt% Y2O3, respectively.
[0108] S2:
[0109] Weigh 1169.22g of boehmite, add 103.92g of 65% nitric acid, and add deionized water to make the boehmite solid content 24wt% and the system pH 3.5.
[0110] Shear dispersion was performed at 2250 r / min for 40 min, and then shear dispersion was continued for another 30 min after adding the composite seed crystal dispersion.
[0111] Degas at -0.0875 MPa for 20 min, then age at 55℃ for 2.5 h.
[0112] S3:
[0113] Extrusion is performed using a die with an aperture of 0.75 mm.
[0114] Dry at 52.5℃ and 70% relative humidity for 4 hours, then dry at 95℃ and -0.0825MPa vacuum for 5 hours.
[0115] The precursor particles were crushed and screened to obtain a particle size of 0.30–1.20 mm.
[0116] S4:
[0117] The temperature was increased to 400℃ at 3.5℃ / min and held for 1 hour, then increased to 990℃ at 7.5℃ / min and held for 1 hour.
[0118] Heat to 1305℃ at 27.5℃ / min and hold for 12.5min; cool to 1130℃ at 40℃ / min and hold for 75min; then cool to below 800℃ at 7.5℃ / min and allow to cool naturally.
[0119] F46 nanocrystalline blue ceramic corundum abrasive was obtained by crushing, shaping and sieving.
[0120] Example 3:
[0121] S1-1:
[0122] Weigh 6.00g of α-Al2O3 powder with a purity of 99.95wt% and a median particle size of 1.0μm, and prepare a slurry with a solid content of 15wt% and a pH value of 4.2.
[0123] Wet grinding was performed using yttrium-stabilized zirconia grinding balls with a particle size of 0.15 mm until the median particle size of α-Al2O3 particles was 20 nm.
[0124] Add 0.048g of polyaspartic acid, which is 0.80wt%, and stir at 50℃ for 90min.
[0125] S1-2:
[0126] Add 6.648g cobalt acetate tetrahydrate, 3.129g aluminum nitrate nonahydrate and 31.560g urea, and add water to make the total concentration of metal ions 0.06mol / L.
[0127] The molar ratio of cobalt to aluminum is 3.2:1, and the molar ratio of urea to the total amount of metal ions is 15:1.
[0128] The reaction was carried out at 98℃ for 10 hours, the final pH value was 9.0, and the local average thickness of the inner layer was 9.8 nm.
[0129] S1-3:
[0130] Dissolve 15.905g magnesium nitrate hexahydrate, 4.071g yttrium nitrate hexahydrate and 47.845g aluminum nitrate nonahydrate in a mixed solvent of water and ethanol, and add 76.926g anhydrous citric acid and 37.278g ethylene glycol.
[0131] The molar ratio of magnesium, yttrium, and aluminum is 5.84:1:12, the molar ratio of citric acid to the total amount of metal ions is 2.0:1, and the molar ratio of ethylene glycol to citric acid is 1.5:1.
[0132] The pH of the system was adjusted to 6.5, and the system was concentrated at 85°C and 25 kPa to form a discontinuous outer layer with a local average thickness of 7.9 nm.
[0133] The powder was vacuum dried at 85℃, then added to deionized water with a pH of 5.8, along with 0.20 wt% polyethylene glycol. The mixture was then ultrasonically and wet-milled to obtain a dispersion with a solid content of 15 wt%. Its D50 was 120 nm and D90 was 200 nm.
[0134] The amount of composite seed crystals added is 0.60 wt%; the amounts of cobalt, magnesium and yttrium added are converted to 0.20 wt% CoO, 0.25 wt% MgO and 0.12 wt% Y2O3, respectively.
[0135] S2:
[0136] Weigh 1161.47g of boehmite, add 150.16g of 65% nitric acid, and add deionized water to make the boehmite solid content 30wt% and pH 4.2.
[0137] Shear at 3000 r / min for 60 min, add composite seed dispersion and continue shearing for 45 min; degas at -0.095 MPa for 30 min, and age at 65℃ for 4 h.
[0138] S3:
[0139] Extrusion was performed using a die with an aperture of 1.2 mm.
[0140] Dry at 60℃ and 80% relative humidity for 6 hours, then dry at 110℃ and -0.095MPa vacuum for 8 hours.
[0141] The precursor particles were crushed and screened to obtain a particle size of 0.50–2.0 mm.
[0142] S4:
[0143] The temperature was increased to 450℃ at a rate of 5℃ / min and held for 1.5 hours, then increased to 1050℃ at a rate of 10℃ / min and held for 1.5 hours.
[0144] Heat to 1335℃ at 40℃ / min and hold for 20min; cool to 1160℃ at 60℃ / min and hold for 120min; then cool to below 800℃ at 10℃ / min and allow to cool naturally.
[0145] F46 nanocrystalline blue ceramic corundum abrasive was obtained by crushing, shaping and sieving.
[0146] Example 4:
[0147] Weigh 6.00g of α-Al2O3 powder with a median particle size of 1.0μm and grind it according to the method in Example 2, but stop grinding when the median particle size of the seed crystal reaches 80nm.
[0148] The amount of polyaspartic acid used is 0.50 wt% of the mass of α-Al2O3.
[0149] Add 1.554g of cobalt nitrate hexahydrate, 0.770g of aluminum nitrate nonahydrate and 4.661g of urea, and control the molar ratio of cobalt to aluminum to be 2.6:1 to form a Co-Al layered double hydroxide inner layer with a local average thickness of 3.9nm.
[0150] The outer layer was prepared using 3.181g magnesium nitrate hexahydrate, 0.678g yttrium nitrate hexahydrate, 5.316g aluminum nitrate nonahydrate, 8.714g anhydrous citric acid and 2.815g ethylene glycol.
[0151] The resulting composite seed dispersion has a D50 of 120 nm and a D90 of 196 nm.
[0152] The amounts of cobalt, magnesium, and yttrium added are equivalent to 0.04 wt% CoO, 0.05 wt% MgO, and 0.02 wt% Y2O3, respectively.
[0153] Except for adjusting the amount of boehmite to 1168.65g, the preparation, shaping, drying and sintering conditions of the wet gel were the same as in Example 2.
[0154] Example 5:
[0155] Except for the cobalt and aluminum sources in the inner layer of the Co-Al layered double hydroxide, the other formulations and process conditions are the same as in Example 2.
[0156] The 4.661g cobalt nitrate hexahydrate in Example 2 was replaced with 3.989g cobalt acetate tetrahydrate.
[0157] In Example 2, 2.311 g of aluminum nitrate nonahydrate was replaced with 2.077 g of an aqueous solution of aluminum acetate with an aluminum content of 8.0 wt%; the molar ratio of cobalt to aluminum was maintained at 2.6:1 according to the molar number of aluminum elements.
[0158] After the reaction, a Co-Al layered double hydroxide inner layer with a local average thickness of 5.6 nm was obtained, and the resulting composite seed crystals had a D50 of 78 nm and a D90 of 147 nm.
[0159] The following comparative examples are all based on Example 2. Each comparative example changes only one core factor, while the remaining raw material content, forming conditions and heat treatment conditions remain unchanged.
[0160] Comparative Example 1:
[0161] Surface-confined composite seed crystals are not prepared.
[0162] 3.50g of α-Al2O3 seed crystals with an average particle size of 50nm were directly added to the pseudoboehmite sol; cobalt nitrate, aluminum nitrate, magnesium nitrate and yttrium nitrate in the same molar amounts as in Example 2 were directly dissolved in water and then added to the same pseudoboehmite sol.
[0163] The total amount of cobalt, magnesium, yttrium and α-Al2O3 seed crystals added was the same as in Example 2, and the remaining steps were the same as in Example 2.
[0164] The only difference between this comparative example and Example 2 is whether the functional components are pre-assembled into surface-confined composite seed crystals.
[0165] Comparative Example 2:
[0166] According to Example 2, α-Al2O3 seed nuclei and Co-Al layered double hydroxide inner layers were prepared, but an outer layer of Mg-Y-Al citric acid polymer complex was not formed on the outside of the inner layer.
[0167] Magnesium nitrate, yttrium nitrate, and aluminum nitrate, in the same amounts as in Example 2, were directly added to the pseudoboehmite sol.
[0168] The total content of Mg, Y and Al in this comparative example is the same as that in Example 2. The only difference is whether the Mg-Y-Al component is pre-positioned in the form of a polymerized complex outer layer.
[0169] Comparative Example 3:
[0170] α-Al2O3 seed nuclei were prepared according to Example 2, and the same Mg-Y-Al citric acid polymer complex outer layer was formed, but Co-Al layered double hydroxides were not grown in situ on the surface of the seed nuclei.
[0171] Cobalt nitrate and aluminum nitrate in the same amounts as in Example 2 were directly added to the pseudoboehmite sol.
[0172] The total cobalt and aluminum content in this comparative example is the same as that in Example 2. The only difference is whether the cobalt and aluminum components are pre-confined in the form of Co-Al layered double hydroxide inner layer.
[0173] Comparative Example 4:
[0174] Precursor particles were prepared according to Example 2.
[0175] After removing organic matter at 400℃, instead of pre-reaction and holding at 990℃, the temperature is directly raised to 1305℃ at the same heating rate for sintering.
[0176] The remaining conditions are the same as in Example 2.
[0177] Comparative Example 5:
[0178] All materials were prepared according to Example 2, but the holding time at 1305°C was extended from 12.5 min to 60 min.
[0179] The remaining conditions are the same as in Example 2.
[0180] Comparative Example 6:
[0181] According to Example 2, the temperature was raised to 1305°C and held for 12.5 minutes. Instead of holding at 1130°C for 75 minutes, the temperature was directly lowered to 800°C at a rate of 7.5°C / min.
[0182] The remaining conditions are the same as in Example 2.
[0183] Performance testing
[0184] This application uses F46 coarse abrasive grains as the uniform test particle size.
[0185] Sampling and reduction of each batch of products were carried out in accordance with GB / T 4676—2018 "Sampling Method for Common Abrasives".
[0186] Samples of F46 particle size were obtained by sieving according to GB / T 2481.1—2025 "Determination and marking of particle size composition of abrasives for bonded abrasives - Part 1: coarse abrasives F4 to F220".
[0187] The contents of Co, Mg, Y and Al were determined according to GB / T 30902—2014 "Determination of Impurity Elements in Inorganic Chemical Products by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES)", and then converted to the contents of CoO, MgO, Y2O3 and Al2O3 respectively.
[0188] Each sample was tested in triplicate, and the arithmetic mean was taken. GB / T 30902—2014 is currently the prevailing standard.
[0189] The crystal phase was tested in accordance with GB / T 30904—2014 "X-ray diffraction method for crystal structure analysis of inorganic chemical products".
[0190] Since the overall content of cobalt aluminum spinel is low, and the X-ray diffraction peaks are not obvious, further selection area electron diffraction and energy dispersive spectroscopy analysis using transmission electron microscopy were used to confirm the presence of CoAl2O4 cobalt aluminum spinel nanocrystal domains.
[0191] The abrasive particles are embedded, ground, polished, and then thermally etched.
[0192] The scanning electron microscope scale was calibrated according to GB / T 20307—2006 "General Rules for Measurement Methods of Nanoscale Lengths by Scanning Electron Microscopy". No less than 5 fields of view were randomly selected for each sample, and no less than 300 α-Al2O3 grains were counted for each sample. The average grain size and D90 grain size were calculated based on the equivalent circle diameter.
[0193] Grains with an equivalent circle diameter greater than 500 nm are defined as abnormally coarse grains, and their proportion is calculated.
[0194] At least 10 regions were randomly selected under a transmission electron microscope to perform energy dispersive spectral scanning of Al, Co, Mg and Y elements.
[0195] A continuous region where the Co signal intensity is three times higher than the average Co signal intensity of the adjacent α-Al2O3 matrix is defined as a Co enrichment region.
[0196] Measure the shortest distance from the geometric center of each Co enrichment region to the nearest α-Al2O3 grain boundary or triangular grain boundary, and count no less than 200 enrichment regions for each sample.
[0197] Calculate the grain boundary localization rate using the following formula:
[0198] Grain boundary location rate = number of Co-enriched regions within 50 nm of the grain boundary or triple grain boundary ÷ total number of Co-enriched regions × 100%.
[0199] The size of the nanocrystalline domains of cobalt aluminum spinel is represented by the equivalent circle diameter in transmission electron microscopy images.
[0200] The density of the abrasive particles was tested according to JB / T 11433—2013 "Determination of density of common abrasives".
[0201] The bulk density was tested in accordance with GB / T 20316.1—2009 "Determination of bulk density of common abrasives - Part 1: coarse abrasive grains".
[0202] Witness test blocks with dimensions of 20 mm × 20 mm × 5 mm were simultaneously prepared from the same wet gels in each embodiment and comparative example. The witness test blocks and the corresponding abrasive precursors were subjected to the same pre-reaction and sintering regimes.
[0203] The apparent porosity of the test specimen was tested according to GB / T 25995—2010 "Test Method for Density and Apparent Porosity of Fine Ceramics".
[0204] The ball milling toughness index of the F46 sample was tested according to GB / T 23538—2023 "Determination of ball milling toughness of common abrasives".
[0205] Each sample was tested in parallel three times, and the average value was taken.
[0206] The crushing resistance of the F46 sample was tested according to JB / T 13944—2020 "Determination of Crushing Resistance of Common Abrasives".
[0207] For each batch, a specified number of abrasive particles are randomly tested, and after removing particles with obvious abnormal shapes, the average value is calculated according to the standard.
[0208] The L*, a*, and b* values of abrasive powder were tested according to GB / T 3979—2008 "Methods for Measurement of Object Color", using a D65 standard illuminator and specified observation conditions.
[0209] Ten reduced samples were randomly obtained from each batch of products, and their colors were measured separately. The average color of the ten samples was taken as the center value, and the color difference between each sample and the center value was calculated according to GB / T 7921—2008 "Uniform Color Space and Color Difference Formula". The color uniformity within the batch was represented by the maximum color difference ΔE*ab.
[0210] The smaller the b value and the more negative the value, the more pronounced the blue hue; the smaller the maximum ΔEab, the better the color uniformity.
[0211] Table 1
[0212] Example 1 0.041 0.052 0.021 148 Example 2 0.119 0.149 0.07 118 Example 3 0.198 0.247 0.119 238 Example 4 0.041 0.051 0.021 222 Example 5 0.12 0.151 0.069 126 Comparative Example 1 0.119 0.15 0.07 325 Comparative Example 2 0.12 0.149 0.071 295 Comparative Example 3 0.118 0.151 0.07 158 Comparative Example 4 0.12 0.15 0.069 210 Comparative Example 5 0.119 0.149 0.071 430 Comparative Example 6 0.121 0.15 0.07 136
[0213] Table 2
[0214] Example 1 235 0.4 16 70 0.72 Example 2 185 0.2 25 83 0.31 Example 3 390 1.8 45 76 0.42 Example 4 345 1.2 30 65 0.56 Example 5 198 0.3 27 80 0.35 Comparative Example 1 690 9.1 92 29 1.18 Comparative Example 2 580 6.5 31 78 0.84 Comparative Example 3 270 1.4 110 22 0.51 Comparative Example 4 405 3.4 82 44 0.75 Comparative Example 5 860 13.1 65 52 0.18 Comparative Example 6 220 0.8 29 69 0.58
[0215] Table 3
[0216] Example 1 3.94 1.88 88.1 41 53.4 −1.8 −11.9 1.18 Example 2 3.96 1.91 92.8 45.9 47.8 −2.5 −15.8 0.61 Example 3 3.95 1.92 86.5 39.6 40.2 −2.9 −20.4 0.84 Example 4 3.94 1.89 84.8 38.5 52.9 −1.9 −12.1 1.29 Example 5 3.96 1.9 91.9 45.1 48.1 −2.4 −15.4 0.69 Comparative Example 1 3.88 1.78 71.8 31.2 49.8 −1.5 −12.7 4.76 Comparative Example 2 3.9 1.82 76.9 33.8 48.5 −2.3 −15.1 1.42 Comparative Example 3 3.93 1.86 83.6 36.9 55.6 −1.2 −10.1 5.43 Comparative Example 4 3.91 1.83 80.2 35 52 −1.6 −11.4 3.62 Comparative Example 5 3.98 1.95 68.7 29.4 45.7 −2.6 −16.3 1.75 Comparative Example 6 3.93 1.86 86 38.8 48.4 −2.3 −15.5 1.05
[0217] Example 2 used the same amount of CoO, MgO, Y2O3, and α-Al2O3 seed crystals as Comparative Example 1, and the sintering process was also the same. The only difference was whether the functional components were pre-assembled into surface-confined composite seed crystals. Compared with Comparative Example 1, the average α-Al2O3 grain size in Example 2 decreased from 325 nm to 118 nm, the proportion of abnormally large grains decreased from 9.1% to 0.2%, the average size of the cobalt-aluminum spinel crystal domains decreased from 92 nm to 25 nm, and the grain boundary localization rate increased from 29% to 83%. The ball milling toughness index of Example 2 increased by approximately 29.2% compared to Comparative Example 1, the average fracture resistance increased by approximately 47.1%, and the maximum color difference decreased from 4.76 to 0.61.
[0218] The above results indicate that the performance improvement does not stem from the increased content of cobalt, magnesium, and yttrium, but rather from the pre-positioning of these three components on the same seed crystal and the resulting spatial synergistic relationship.
[0219] Comparative Example 2 retained the Co-Al layered double hydroxide inner layer and kept the total amounts of Mg, Y, and Al unchanged, only adding the Mg-Y-Al component directly to the pseudoboehmite sol. The cobalt-aluminum spinel grain boundary localization rate of Comparative Example 2 remained at 78%, indicating that the Co-Al inner layer could still restrict the position of the cobalt component; however, its average α-Al₂O₃ grain size increased to 295 nm, the proportion of abnormally coarse grains reached 6.5%, and the ball milling toughness index decreased to 76.9%. This shows that whether the Mg and Y components are pre-distributed in the form of an outer layer has a decisive influence on the grain boundary suppression effect. Simply maintaining the same overall chemical composition cannot achieve the same grain boundary control effect as the composite outer layer.
[0220] Comparative Example 3 retained the outer layer of the Mg-Y-Al polymer complex and kept the total amount of cobalt and aluminum added unchanged, but directly added cobalt and aluminum salts to the pseudoboehmite sol. The average α-Al2O3 grain size of Comparative Example 3 could still be maintained at 158 nm, indicating that the Mg and Y components in the outer layer could inhibit some grain growth; however, its cobalt-aluminum spinel crystal domain increased to 110 nm, the grain boundary localization rate decreased to 22%, and the maximum color difference reached 5.43.
[0221] This indicates that the main contribution of the Co-Al inner layer is not simply to provide cobalt, but to restrict the migration, aggregation, and reaction sites of the cobalt colorimetric precursor, thereby obtaining smaller colorimetric crystal domains and a more uniform blue color.
[0222] Comparative Example 4 only omitted the 990℃ pre-reaction heat treatment. Its cobalt-aluminum spinel crystal domain increased to 82nm, the grain boundary positioning rate decreased to 44%, the maximum color difference increased to 3.62, and the apparent porosity and the proportion of abnormally large grains were both higher than those in Example 2.
[0223] The reason is that, after the pre-reaction is eliminated, the formation of cobalt-aluminum spinel, alumina phase transformation, and particle densification occur concentrated in the stage of rapid heating to 1305℃. The cobalt component aggregates more significantly under high-temperature liquid phase or high diffusion rate conditions, while the competition between the color reaction and densification also reduces the uniformity of the microstructure.
[0224] Comparative Example 5 only extended the holding time at 1305℃ from 12.5 min to 60 min. The particle density and bulk density of Comparative Example 5 were slightly higher than those of Example 2, and the apparent porosity decreased to 0.18%, indicating that extending the holding time could improve the densification degree; however, its average grain size increased to 430 nm, the proportion of abnormally coarse grains reached 13.1%, and the ball milling toughness index and crushing resistance decreased to 68.7% and 29.4 N, respectively.
[0225] This demonstrates that higher density does not necessarily equate to better performance in ceramic corundum abrasives. While prolonged holding at the highest temperature reduces residual porosity, it also leads to abnormal grain growth, reducing the number of controllable micro-fracture units within the abrasive grains and consequently decreasing ball milling toughness and resistance to breakage.
[0226] Comparative Example 6 only omitted the 1130℃ grain boundary stabilization insulation. Compared with Example 2, the average grain size of Comparative Example 6 increased only slightly, but the apparent porosity, the proportion of abnormal grains, and the maximum color difference all increased, and the ball milling toughness index decreased from 92.8% to 86.0%.
[0227] like Figure 1 As shown in the figure, the relatively deep particles are α-Al₂O₃ seed nuclei. Discontinuous plate-like or island-like gray-scale contrast areas can be observed on the surface of the seed nuclei, and there are also shallower coating areas at their outer edges, indicating that the prepared composite seed has a core particle and a discontinuous surface coating structure. No large-area dense sintered necks are observed between the composite seed particles, and the particles as a whole maintain an independent dispersed state.
[0228] Depend on Figure 2 It can be observed that the Al element signal covers the main region of the composite seed crystal, while the Co element signal is mainly distributed around the seed nucleus, exhibiting a discontinuous ring or plate-like distribution. The Mg and Y element signals are mainly distributed in the outer region of the composite seed crystal, partially overlapping with the Co element region. No large-sized Co, Mg, or Y enriched particles significantly independent of the α-Al₂O₃ seed nucleus were observed. The above elemental distribution results indicate that the Co, Mg, and Y components are not simply mixed in the form of independent large particles, but rather form a spatially correlated surface distribution structure around the Al-containing seed nucleus. Specifically, the Co element distribution supports the formation of the inner layer of the Co-Al layered double hydroxide, while the distribution of Mg and Y elements around the particle periphery supports the formation of the outer layer of the Mg-Y-Al citric acid polymer complex.
[0229] This indicates that grain boundary stabilization treatment is mainly used to promote the redistribution of grain boundary control components, stabilize grain boundaries, and eliminate local microstructure differences under conditions below the maximum densification temperature, rather than simply continuing sintering.
Claims
1. A method for preparing nanocrystalline blue ceramic corundum abrasive, characterized in that, Includes the following steps: S1. Preparation of surface-confined composite seed crystals: Using α-Al2O3 particles with an average particle size of 20-80 nm as seed crystal nuclei, a discontinuous Co-Al layered double hydroxide inner layer is grown in situ on the surface of the seed crystal nuclei, and then a Mg-Y-Al citric acid polymer complex outer layer is formed on the outside of the Co-Al layered double hydroxide inner layer to obtain surface-confined composite seed crystals. Based on the mass of Al2O3 in the final abrasive, the amount of α-Al2O3 seed nuclei added is 0.15–0.60 wt%, the cobalt content in the inner layer of the Co-Al layered double hydroxide is 0.04–0.20 wt% (calculated as CoO), the magnesium content in the outer layer of the Mg-Y-Al citric acid polymer complex is 0.05–0.25 wt% (calculated as MgO), and the yttrium content is 0.02–0.12 wt% (calculated as Y2O3). S2. Preparation of alumina wet gel containing composite seed crystals: Boehmite, water and nitric acid are mixed to prepare a boehmite sol with a solid content of 18-30 wt% and a pH value of 2.8-4.
2. The surface-confined composite seed crystals obtained in step S1 are dispersed in the boehmite sol. After shear dispersion, vacuum degassing and heating aging, alumina wet gel containing composite seed crystals is obtained. S3. The alumina wet gel is shaped and subjected to gradient drying, crushed and sieved to obtain ceramic corundum precursor particles. S4. The ceramic corundum precursor particles are placed in an oxygen-containing atmosphere and pre-reacted at 900-1050°C to transform the inner layer of the Co-Al layered double hydroxide into CoAl2O4 nanocrystalline domains and the outer layer of the Mg-Y-Al citric acid polymer complex into a magnesium- and yttrium-containing grain boundary regulating phase precursor. The temperature was then raised to 1250–1340℃ for short-term densification sintering, and then lowered to 1080–1160℃ for grain boundary stabilization treatment. After cooling, sieving, and classification, nanocrystalline blue ceramic corundum abrasive was obtained.
2. The method for preparing a nanocrystalline blue ceramic corundum abrasive according to claim 1, characterized in that, The α-Al2O3 seed nuclei were prepared according to the following method: α-Al2O3 powder with a purity of not less than 99.9 wt% and a median particle size of 0.2–1.0 μm was added to a nitric acid aqueous solution to prepare a slurry with a solid content of 5–15 wt% and a pH value of 3.0–4.
2. Yttrium-stabilized zirconia grinding balls with a particle size of 0.05–0.15 mm were added for wet grinding until the median particle size of the α-Al2O3 particles in the slurry was 20–80 nm. Add 0.20–0.80 wt% polyaspartic acid relative to the mass of α-Al2O3 to the ground slurry, and stir at 30–50 °C for 20–90 min to allow the polyaspartic acid to adsorb onto the surface of the α-Al2O3 particles, thus obtaining a surface-carboxylated α-Al2O3 seed nucleus dispersion.
3. The method for preparing a nanocrystalline blue ceramic corundum abrasive according to claim 2, characterized in that, The Co-Al layered double hydroxide inner layer was prepared according to the following method: Soluble cobalt salt, soluble aluminum salt, and urea are added to the α-Al2O3 seed nucleus dispersion, wherein the molar ratio of cobalt ions to aluminum ions is 2.0∶1~3.2∶1, the total concentration of cobalt ions and aluminum ions is 0.01~0.06mol / L, and the molar ratio of urea to the total amount of cobalt ions and aluminum ions is 6∶1~15∶1; The resulting mixture was reacted at 85–98 °C for 4–10 h to gradually increase the pH of the reaction system to 7.5–9.0, and to allow the Co-Al layered double hydroxide to preferentially nucleate on the surface of the α-Al2O3 seed crystals, forming a discontinuous nanosheet inner layer with a thickness of 2–10 nm. The soluble cobalt salt is at least one of cobalt nitrate and cobalt acetate, and the soluble aluminum salt is at least one of aluminum nitrate and aluminum acetate.
4. The method for preparing a nanocrystalline blue ceramic corundum abrasive according to claim 3, characterized in that, The outer layer of the Mg-Y-Al citric acid polymer complex was prepared according to the following method: Magnesium nitrate, yttrium nitrate, and aluminum nitrate were dissolved in a mixed solvent of water and ethanol. Citric acid and ethylene glycol were then added to obtain a Mg-Y-Al complex solution, wherein the molar ratio of magnesium, yttrium, and aluminum was 3–8:1:4–12, the molar ratio of citric acid to the total amount of magnesium, yttrium, and aluminum was 1.2–2.0:1, and the molar ratio of ethylene glycol to citric acid was 0.5–1.5:
1. The pH of the Mg-Y-Al complex solution was adjusted to 5.5–6.5, and α-Al2O3 seed nuclei with an inner layer of Co-Al layered double hydroxides on the surface were added. The solution was stirred and concentrated at 70–85°C under reduced pressure to allow citric acid and ethylene glycol to undergo condensation polymerization and cause the Mg-Y-Al polymer complex to be adsorbed onto the outer side of the inner layer of the Co-Al layered double hydroxides, forming a discontinuous outer layer with a thickness of 1–8 nm.
5. The method for preparing a nanocrystalline blue ceramic corundum abrasive according to claim 4, characterized in that, The surface-confined composite seed crystals are further processed according to the following method: The material after forming the outer layer of the Mg-Y-Al citric acid polymer complex is vacuum dried at 60-85℃ to obtain composite seed powder; the composite seed powder is added to deionized water with a pH of 4.5-5.8, and ultrasonically dispersed and wet-milled in the presence of polyethylene glycol at 0.05-0.20 wt% relative to the mass of the composite seed powder to obtain a composite seed dispersion with a solid content of 5-15 wt%; The median particle size of the composite seed in the composite seed dispersion is 35–120 nm, and the particle size D90 is not greater than 200 nm.
6. The method for preparing a nanocrystalline blue ceramic corundum abrasive according to claim 1, characterized in that, In step S2: The purity of the pseudoboehmite is not less than 99.5 wt%, the specific surface area is 180–320 m² / g, and the Na₂O content is not higher than 0.05 wt%. The molar ratio of nitric acid to AlOOH in pseudoboehmite is 0.03–0.08:1; First, boehmite is added to an aqueous nitric acid solution and sheared and dispersed at 1500–3000 r / min for 20–60 min. Then, the composite seed crystal dispersion is added and sheared and dispersed for another 15–45 min. The mixture is then degassed for 10–30 min under a vacuum of -0.080–-0.095 MPa and subsequently aged at 45–65 °C for 1–4 h to obtain the alumina wet gel.
7. The method for preparing a nanocrystalline blue ceramic corundum abrasive according to claim 1, characterized in that, In step S3: The alumina wet gel was extruded through a mold with a pore size of 0.3-1.2 mm, and dried in the first stage for 2-6 hours at 45-60°C and 60-80% relative humidity, and then dried in the second stage for 2-8 hours at 80-110°C and -0.070 to -0.095 MPa vacuum. The dried gel was crushed and sieved to obtain ceramic corundum precursor particles with a particle size of 0.15–2.0 mm.
8. The method for preparing a nanocrystalline blue ceramic corundum abrasive according to claim 1, characterized in that, The pre-reaction calcination in step S4 includes: The temperature is increased to 350–450°C at a rate of 2–5°C / min and held for 0.5–1.5 h to decompose the organic components in the outer layer of the Mg-Y-Al citric acid polymer complex. The temperature is then increased to 930–1050℃ at a rate of 5–10℃ / min and held for 0.5–1.5 h. This results in a Co-Al layered double hydroxide with a Co / Al molar ratio of 2.0–3.2, which is a cobalt-rich precursor. After calcination, it may first form a mixed oxide containing cobalt aluminum spinel, and then react with the adjacent α-Al2O3 seed nucleus and alumina matrix to finally form a cobalt aluminum spinel nanocrystal domain containing CoAl2O4.
9. The method for preparing a nanocrystalline blue ceramic corundum abrasive according to claim 8, characterized in that, The short-time densification sintering and grain boundary stabilization treatment in step S4 includes: The pre-reacted calcined precursor particles were heated to 1270–1335°C at a heating rate of 15–40°C / min and held for 5–20 min. Then, the temperature is lowered to 1100–1160°C at a rate of 20–60°C / min, held for 30–120 min, and then cooled to below 800°C at a rate of no more than 10°C / min before naturally cooling to room temperature.
10. A nanocrystalline blue ceramic corundum abrasive, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 9.